Evaluating the role of kangaroo mother care on the lactation among the newborn low birth weight babies - Margekar, Purnima; Parekh, Premlata; Margekar, Shubha Laxmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: A universally available and biologically sound method of care for all new-borns, but in particular for premature babies, with three components including skin-to-skin contact, exclusive breastfeeding and support to the “mother infant dyad”. The present study was done to evaluate the role of kangaroo mother care (KMC) on the lactation. Methods: A prospective case control study of KMC was conducted in a teaching institution with a tertiary level neonatal intensive care unit (NICU) over a 12-month period from August 2013 to August 2014 on 50 new-borns weighing less than 1.8 kg. In order to provide KMC, special bag or kangaroo pouch was designed to keep the baby in close contact with mother. The primary outcome variable was “breast feeding”. Mode of feeding at admission to either group was noted down. Before allocating to either group, it was assured that baby was tolerating enteral feeds & there was no regurgitation. Results: Sixty six percent of neonates in case group and eighty percent of control group were on tube feed while 30% of case group and 16% of control group were on spoon feed at the time of enrolment in study. Spoon feeding plus breast feeding was established 28% of KMC group and in 4% control group, while only breast feeding was established in 30% of KMC group and 26% of control group on discharge. Conclusions: More babies in KMC group were shifted to breast-feeding on discharge. In addition to that KMC group demonstrated more weight gain and duration of stay was shorter in them.